PERANAN KEARIFAN LOKAL DALAM PENYELESAIAN SENGKETA PERTANAHAN - Herry Anto Simanjuntak, SH, MH (JURNAL JUSTIQA, 2021)
Land is where we stand so that the role of land is very urgent in daily life and people view land not only from an economic perspective but also from another perspective, namely in the perspective of cultural religiosity and ecology. The role of local wisdom values in land dispute resolution can be a model for civil mediation in various national agrarian cases. The role of local wisdom is to uphold human rights based on customs, the spirit of mutual cooperation and moral ethics that grow in the community. In this case the approach in terms of legal anthropology becomes an interesting thing to use. In the future, land dispute resolution with a civil mediation model refers to the values of local wisdom. With the principle of deliberation, it aims to involve or invite all parties to participate in social life, so that the community's loyalty and obedience to what is mutually agreed upon will also be maintained together, because the agreement was the fruit of shared thoughts and opinions in a family atmosphere and mutual respect These fellows and local wisdom values are expected to maintain a complete and complete unity between Man, Nature and God, in spiritual nuances, peace and brotherhood.